Mockingjay - Collins, Suzanne (New York : Scholastic Press, 2010)
Katniss Everdeen's having survived the Hunger games twice makes her a target of the Capitol and President Snow, as well as a hero to the rebels who will succeed only if Katniss is willing to put aside her personal feelings and serve as their pawn.
Keywords: Insurgency -- Fiction; Survival -- Fiction; Television programs -- Fiction; Interpersonal relations -- Fiction; Contests -- Fiction; Science fiction